Aiding education? The effect of international aid on local educational enrolment in Nigeria - Roos van der Haer; Gudrun Østby (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Education is associated with a range of positive micro and macro effects. It is hence no surprise that donors have recently increased the amount of official development aid specifically focused on restoring and maintaining education in less-developed states. While much attention has been paid to the effect of aid on educational enrolment at the country level, there is a clear knowledge gap at the subnational level. To fill this gap, we examine the impact on educational enrolment of geographical proximity to aid projects by combining individual-level information on education from six Nigerian Demographic and Health Surveys with spatio-temporal data from AidData on the precise location and timing of aid projects in Nigeria for the period 1990-2015. Using quasi-experimental approaches, with difference-in-differences estimates using information on active and inactive aid locations, we control for a vast number of unobserved factors that might otherwise be spuriously correlated with both education and aid. The results suggest that geographical proximity to active aid projects at school-starting age increases the probability that an individual will enrol in school, at both primary and secondary levels. The effect of aid on school enrolment is particularly pronounced for individuals from less-wealthy backgrounds. We also find evidence for a clear selection effect: aid disproportionately reaches areas with higher enrolment rates in the first place. Our findings have important implications for understanding the link between conflict, aid, and educational disruption and could have important consequences for the future spending of donors.
Keywords: I22; I24; C12; 330; aid; education; enrolment; Nigeria; Africa